Does Parental Involvement Affect The Development Of Social Skills In Early Childhood Education Students? - Supriatna, Ecep; Aprianti, Ema (IKIP Siliwangi, 2025)
This study aims to examine the effect of parental involvement on social skills in early childhood education students in Bandung City (1). The research approach uses quantitative with a comparative study method that compares two groups of children based on their parental involvement (3). The sampling technique used is convenience sampling. This technique selects respondents who are easy to reach and willing to participate. This study involved 227 parents who assessed their involvement in their children's education through a self-report scale, and 34 early childhood education teachers who assessed their children's social skills through observation (2). The instruments used consisted of a parental involvement scale and an observation-based social skills scale. Data analysis used the Mann-Whitney U nonparametric statistical test to see differences in children's social skills based on the level of parental involvement. The results showed that there were significant differences in the social skills of early childhood education students between children with high and low parental involvement (5). Children with higher parental involvement tend to have better social skills. This topic is important to study considering the role of parents in early childhood education is a key factor in forming social skills that are important for children's development in the future